Perioperative and anesthesia adverse events in thailand [Paad Thai] incident reporting study: Unplanned ICU admission analysis - Thanist Pravitharangul (2018)
© 2018, Medical Association of Thailand. All rights reserved. Objective: To study of anesthetic outcomes and patient characteristics, events, and factors to determine the risks related to unplanned intensive care unit [ICU] admission after anesthesia. Materials and Methods: The present study was a part of the Perioperative and Anesthetic Adverse events in Thailand [PAAd Thai] study. This is a prospective observational study analysis of structured case record form. Data collection was conducted in 22 hospitals across Thailand between January and December 2015. Baseline characteristics, details of anesthesia, type of procedure, and adverse events were recorded and analyzed to determine risks related to unplanned ICU admission after anesthesia. Results: Rate of unplanned ICU admission was 4.3:10,000 anesthetic procedures. Cardiac arrest within 24 hours post-anesthesia had highest relative risk of 9.36. The other significant factors were elder age, duration longer than 120 minutes, higher ASA physical status (III, IV, V), overtime, emergency procedure, cardiac surgery, general surgery, vascular surgery, desaturation within 24 hours post-anesthesia, reintubation within 24 hours post-anesthesia, neurological complication within 24 hours post-anesthesia, myocardial ischemia within 24 hours post-anesthesia, and cardiac arrest within 24 hours post-anesthesia. After risk adjustment, the significant predictive factors were higher ASA physical status (III, IV, V), long anesthetic duration (longer than 120 minutes), vascular surgery, reintubation within 24 hours post-anesthesia, and cardiac arrest within 24 hours post-anesthesia. Reintubation within 24 hours post-anesthesia had the highest odds ratio of 8.36. Conclusion: The predictive factors for unplanned ICU admission after anesthesia in Thailand were higher ASA physical status (III, IV, V), long anesthetic duration (longer than 120 minutes), vascular surgery, reintubation within 24 hours post-anesthesia, and cardiac arrest within 24 hours post-anesthesia.